Effects of a randomized controlled trial of mobile app-based Acceptance and Commitment Therapy on depressive symptoms and process variables in college students - Focusing on the mediating effects of acceptance and cognitive defusion- - Jeong, Narae; Kim, Eunjung; Chun, Jonghoon (Journal of Contextual Behavioral Science, 2024)
As social costs rise due to the increasing prevalence of depression, there is a growing emphasis on cost-effective and evidence-based psychotherapeutic methods. Acceptance and Commitment Therapy (ACT) for depression is an effective approach that reduces depressive symptoms and helps prevent recurrence by enhancing psychological flexibility. This study developed a mobile app-based ACT and tested its effectiveness for college students with depression. Eighty college students with depression were randomly assigned to either a treatment group (n = 41) or a control group (n = 39). The treatment group received mobile app-based ACT for 4 weeks, the control group waited without treatment. The scores from pre, post, and follow-up assessments were compared between the two groups. Significant interaction effects of time and group were found for depression and anxiety symptoms, as well as for treatment process variables such as acceptance, inflexibility, defusion, values, commitment, and mindfulness. Acceptance and cognitive defusion emerged as significant mediators in the impact of mobile app-based ACT on depression. The mobile app-based ACT effectively reduced depression and improved treatment process variables, demonstrating its cost-effectiveness. The study also discusses the implications, limitations, and directions for future research.